Identification and Functional Annotation of Genes Differentially Expressed in the Reproductive Tissues of the Olive Tree (Olea europaea L.) through the Generation of Subtractive Libraries - Zafra, Adoración; Carmona, Rosario; Traverso, José A.; Hancock, John T.; Goldman, Maria H. S.; Claros, M. Gonzalo; Hiscock, Simon J.; Alche, Juan D. (Frontiers in Plant Science, 2017)
The olive tree is a crop of high socio-economical importance in the Mediterranean area. Sexual reproduction in this plant is an essential process, which determines the yield. Successful fertilization is mainly favored and sometimes needed of the presence of pollen grains from a different cultivar as the olive seizes a self-incompatibility system allegedly determined of the sporophytic type. The purpose of the present study was to identify key gene products involved in the function of olive pollen and pistil, in order to help elucidate the events and signaling processes, which happen during the courtship, pollen grain germination, and fertilization in olive. The use of subtractive SSH libraries constructed using, on the one hand one specific stage of the pistil development with germinating pollen grains, and on the other hand mature pollen grains may help to reveal the specific transcripts involved in the cited events. Such libraries have also been created by subtracting vegetative mRNAs (from leaves), in order to identify reproductive sequences only. A variety of transcripts have been identified in the mature pollen grains and in the pistil at the receptive stage. Among them, those related to defense, transport and oxidative metabolism are highlighted mainly in the pistil libraries where transcripts related to stress, and response to biotic and abiotic stimulus have a prominent position. Extensive lists containing information as regard to the specific transcripts determined for each stage and tissue are provided, as well as functional classifications of these gene products. Such lists were faced up to two recent datasets obtained in olive after transcriptomic and genomic approaches. The sequences and the differential expression level of the SSH-transcripts identified here, highly matched the transcriptomic information. Moreover, the unique presence of a representative number of these transcripts has been validated by means of qPCR approaches. The construction of SSH libraries using pistil and pollen, considering the high interaction between male-female counterparts, allowed the identification of transcripts with important roles in stigma physiology. The functions of many of the transcripts obtained are intimately related, and most of them are of pivotal importance in defense, pollen-stigma interaction and signaling.